Grand Desain, Inisiasi Wisata Halal dan Edukasi Pasar Ternak Kedung Berkah Dalam Peningkatan Pendapatan Bumdes Desa Tirta Kencana Kecamatan Rimbo Bujang Kabupaten Tebo - Ridhwan, Ridhwan; Amir, Amri; Rafiqi, Rafiqi; Alissa, Evalina; Amri, Ary Dean; Inggriani Powa, Natasya (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
This community service program aims to improve the economic well-being of the residents of Tirta Kencana Village through the development of halal tourism and livestock market education. The strategies implemented include the construction of Muslim-friendly tourism infrastructure, community training on halal tourism standards, and education for livestock farmers to enhance livestock productivity and market access. Through the "Grand Design," the program maps the village's potential and designs sustainable management strategies. The results of this program demonstrate an increase in the community's capacity to provide tourism services and market livestock products, a rise in the number of visiting tourists, and increased income for the Village-Owned Enterprises (BUMDES) as drivers of the local economy. This program has also succeeded in raising community awareness of the importance of environmentally friendly tourism and the role of BUMDES in fostering the village's economic independence. With these efforts, Tirta Kencana Village is expected to serve as a model for competitive halal tourism villages at the national level.